Pengaruh Kepemimpinan Kepala Sekolah, Lingkungan Kerja dan Komunikasi Interpersonal terhadap Kinerja Guru di SMK Muhammadiyah Kabupaten Wonosobo - Muhamad Bahri Irawan; Tri Kuat; Edhy Susatya; Fitri Nur Mahmudah (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine the influence of the principal's leadership, work environment, and interpersonal communication on teacher performance at SMK Muhammadiyah Wonosobo Regency.  The methodology in this study uses quantitative methods. The population in this study was 75 teachers using Issac and Michael's table so that the number of samples was obtained as many as 63 people and then determined based on proportional random sampling. This research instrument uses a closed questionnaire based on the Likert scale. Hypothesis testing is performed based on t-test, F-test, and determination coefficient test. The results of the study based on multiple linear regression analysis showed that the principal's leadership, work environment, and interpersonal communication together had a significant and positive effect on teacher performance with an R Square result of 0.460. However, the results of the t-test showed that the principal's leadership had no partial effect on teacher performance. The t-test also showed that the work environment had no significant effect on teacher performance. Partially, only interpersonal communication showed a positive and significant influence on teacher performance